Gestión financiera con relación a la rentabilidad de la bananera Gaby en el periodo 2010-2012 cantón La Maná provincia de Cotopaxi - Zambrano Mendoza, Lisbeth Fernanda (2014)
This thesis deals with Financial Management with respect to the performance of the Banana Gaby in the period 2010 - 2012 in the Canton La Maná Cotopaxi Province, carried out in order to analyze financial statements and financial indicators and strategies employed in order to determine the solvency, liquidity and profitability obtained during this period. Based on these results the Financial Analysis of the Banana Gaby is a management tool for efficient management decisions by its owner and contribute to better management of economic and financial resources. The implementation of a system of control of economic resources through financial analysis, and analysis of the strategies employed attached to procedures and technical processes, enables efficient and timely management of these resources, leading to optimization, efficiency and effectiveness within the financial and economic management. Furthermore the rational use of financial economic resources that lead to satisfaction and quality in the delivery of the fruit, strengthening the image of the banana and the market acceptance is achieved. Finally the owner manager is recommended to take into account the result of the research conducted, which contribute to improving the administrative, financial and economic management, which in turn is useful for decision-making, and successful development of the Banana recommendations.